Intramembrane Proteolysis by γ-Secretase - Steiner, Harald (American Society for Biochemistry and Molecular Biology, 2008)
γ-Secretase mediates the final proteolytic cleavage, which liberates amyloid β-peptide (Aβ), the major component of senile plaques in the brains of Alzheimer disease patients. Therefore, γ-secretase is a prime target for Aβ-lowering therapeutic strategies. γ-Secretase is a protein complex composed of four different subunits, presenilin (PS), APH-1, nicastrin, and PEN-2, which are most likely present in a 1:1:1:1 stoichiometry. PS harbors the catalytically active site, which is critically required for the aspartyl protease activity of γ-secretase. Moreover, numerous familial Alzheimer disease-associated mutations within the PSs increase the production of the aggregation-prone and neurotoxic 42-amino acid Aβ. Nicastrin may serve as a substrate receptor, although this has recently been challenged. PEN-2 is required to stabilize PS within the γ-secretase complex. No particular function has so far been assigned to APH-1. The four components are sufficient and required for γ-secretase activity. At least six different γ-secretase complexes exist that are composed of different variants of PS and APH-1. All γ-secretase complexes can exert pathological Aβ production. Assembly of the γ-secretase complex occurs within the endoplasmic reticulum, and only fully assembled and functional γ-secretase complexes are transported to the plasma membrane. Structural analysis by electron microscopy and chemical cross-linking reveals a water-containing cavity, which allows intramembrane proteolysis. Specific and highly sensitive γ-secretase inhibitors have been developed; however, they interfere with the physiological function of γ-secretase in Notch signaling and thus cause rather significant side effects in human trials. Modulators of γ-secretase, which selectively affect the production of the pathological 42-amino acid Aβ, do not inhibit Notch signaling.